On Degree Based Topological Indices of Polycyclic Certain Interconnection Networks. (26th November 2022) - Zhang, Wei; Kirmani, Syed Ajaz K.; Siddiqui, Muhammad Kamran; Rauf, Abdul; Aleem, Muhammad; Rashid, Muhammad Aamer
Abstract: Topological indices are the significant numerical quantities in the fields of chemical graph theory. Quantitative structure-property and structure-activity relationships of the Honeycomb Network, Hexagonal Network and Silicate Network SiO4 necessitate expressions for the molecular topological features of these networks. ev-degree and ve-degree established topological indices demarcated as analogous to their relating spouses. In this paper, we have computed topological indices based on ev-degree and ve-degree for the Honeycomb Network, Hexagonal Network and Silicate Network.